2018
DOI: 10.1021/acs.jpclett.8b00808
|View full text |Cite
|
Sign up to set email alerts
|

Precise Control of Local Spin States in an Adsorbed Magnetic Molecule with an STM Tip: Theoretical Insights from First-Principles-Based Simulation

Abstract: The precise tuning of local spin states in adsorbed organometallic molecules by a mechanically controlled scanning tunneling microscope (STM) tip has become a focus of recent experiments. However, the underlying mechanisms remain somewhat unclear. We investigate theoretically the STM tip control of local spin states in a single iron(II) porphyrin molecule adsorbed on the Pb(111) substrate. A combined density functional theory and hierarchical equations of motion approach is employed to simulate the tip tuning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 93 publications
2
61
0
1
Order By: Relevance
“…This is particularly important for the studies on precise control or fine-tuning of local quantum states in nanostructures. For instance, in the past few years, the competition between Kondo resonance and local spin excitations in magnetic molecular QDs has become a focus of experimental efforts [60]. Parks et al have demonstrated that, by stretching a molecular QD embedded in an MCBJ, the Kondo conductance peak is gradually split by enhancing the spin-orbit coupling [61].…”
Section: Scope Of the Reviewmentioning
confidence: 99%
“…This is particularly important for the studies on precise control or fine-tuning of local quantum states in nanostructures. For instance, in the past few years, the competition between Kondo resonance and local spin excitations in magnetic molecular QDs has become a focus of experimental efforts [60]. Parks et al have demonstrated that, by stretching a molecular QD embedded in an MCBJ, the Kondo conductance peak is gradually split by enhancing the spin-orbit coupling [61].…”
Section: Scope Of the Reviewmentioning
confidence: 99%
“…71,72 The HEOM approach has been widely used to study a variety of static and dynamic properties of strongly correlated quantum impurity systems in and out of equilibrium. 62,63,[73][74][75][76][77][78][79] In the framework of the HEOM, the influence of the noninteracting leads on the impurity is fully captured by the hybridization functions, Γ α (ω) ≡ π k |t αk | 2 δ(ω − ǫ αk ). For numerical convenience, a Lorentzian form of Γ α (ω) = ∆αW 2 α (ω−Ωα) 2 +W 2 α is adopted, where ∆ α is the effec-tive coupling strength between the impurity and the αth lead, and Ω α and W α are the band center and width of the αth lead, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The DFT+HEOM approach has been successfully applied to describe the Kondo spin-screening effect in magnetic atom adsorbed on the metal support. 22,42,43 Density functional theory calculation. The Perdew-Burke-Ernzerholf (PBE) generalized gradient approximation implemented in the Vienna ab initio simulation package 44 is employed, with the DFT-D3 method of Grimme 45 used to improve the description of van der Waals interactions.…”
Section: Methodsmentioning
confidence: 99%